2021
DOI: 10.3390/polym13142324
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of p-Phenylenediamine Modified Graphene Foam/Polyaniline@Epoxy Composite with Superior Thermal and EMI Shielding Performance

Abstract: With the development of integrated devices, the local hot spot has become a critical problem to guarantee the working efficiency and the stability. In this work, we proposed an innovative approach to deliver graphene foam/polyaniline@epoxy composites (GF/PANI@EP) with improvement in the thermal and mechanical property performance. The graphene foam was firstly modified by the grafting strategy of p-phenylenediamine to anchor reactive sites for further in-situ polymerization of PANI resulting in a conductive ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…The peaks at 1715 cm −1 , 1580 cm −1 , 1210 cm −1 , and 1153 cm −1 corresponded with the CvO stretching vibration of the carboxylic groups, bending vibration of the hydroxyls and the stretching vibration of the epoxide and alkoxy in GO, respectively. 46 On the other hand, the new sharp IR bands at 3333 cm −1 , 1497 cm −1 , and 1130 cm −1 in the PPD-rGO spectrum corresponding to the vibrations of the N-H and C-N groups, respectively, confirmed that PPD was successfully incorporated into the GO sheets. Typically, during PPD treatment, the formation of C-NH-C bands would happen on the GO surface via a nucleophilic substitution reaction between the amine group of PPD and the epoxide group of GO.…”
Section: Dalton Transactions Papermentioning
confidence: 90%
“…The peaks at 1715 cm −1 , 1580 cm −1 , 1210 cm −1 , and 1153 cm −1 corresponded with the CvO stretching vibration of the carboxylic groups, bending vibration of the hydroxyls and the stretching vibration of the epoxide and alkoxy in GO, respectively. 46 On the other hand, the new sharp IR bands at 3333 cm −1 , 1497 cm −1 , and 1130 cm −1 in the PPD-rGO spectrum corresponding to the vibrations of the N-H and C-N groups, respectively, confirmed that PPD was successfully incorporated into the GO sheets. Typically, during PPD treatment, the formation of C-NH-C bands would happen on the GO surface via a nucleophilic substitution reaction between the amine group of PPD and the epoxide group of GO.…”
Section: Dalton Transactions Papermentioning
confidence: 90%
“…Conducting 3D networks at lower mass concentration of filler have been prepared by modifying GF using p -phenylenediamine (PPD), which anchors the reactive sites on GF for further in situ polymerization of PANI, leading to the formation of the network structure of GF/PANI. 79 It is speculated that PANI promoted the connection of graphene sheets in GF, enabling the formation of the connecting network. After being compounded with epoxy, GF/PANI exhibited an EMI SE value of 38.32 dB.…”
Section: D Graphene Aerogel/foam-based Polymer Composites For Emi Shi...mentioning
confidence: 99%
“…Polymer based graphene composites is an important application field because graphene could increase the properties of composites such as mechanical properties [ 1 , 2 ], electrical performances [ 3 , 4 ], thermal properties [ 5 , 6 ], barrier properties [ 7 , 8 ], flame retardancy [ 9 , 10 ], biomedical applications [ 11 , 12 ], etc. For example, Vasile et al [ 13 ] functionalized graphene oxide with 2-hydroxyethyl methacrylate (HEMA) to prepare a composite with a poly(propylene fumarate)/poly(ethylene glycol) dimethacrylate (PPF/PEGDMA) matrix.…”
Section: Introductionmentioning
confidence: 99%